Treatment completion of drug-resistant tuberculosis in Ethiopia: A perspective from healthcare users. - Ahmed Reshid Tusho; Sheila Theresa Mokoboto-Zwane (PLOS Global Public Health)
Drug-resistant tuberculosis remains a persistent public health threat. Maximizing successful treatment completion is a global health priority and a focus of the End TB strategy. Despite the implementation of programmatic management for drug-resistant tuberculosis in Ethiopia, there is limited understanding of the barriers related to successful treatment completion among Ethiopian patients. A qualitative study that is explorative, descriptive and contextual in nature was conducted to explore and describe the views and lived experiences of previously treated drug-resistant tuberculosis patients to gain an in-depth understanding of barriers to the successful completion of drug-resistant tuberculosis treatment. Six focus group discussion sessions with 42 purposively selected drug-resistant tuberculosis patients with previous treatment history and on retreatment regimens were conducted. The seven prominent themes revealed were: drug-related challenges encompassing adverse events and the lengthy treatment duration; clinical hurdles such as delayed consultation following prolonged illness, diagnostic delays, and suboptimal dosages; psycho-emotional difficulties including emotional trauma and facing stigma from both the community and healthcare professionals; socio-economic constraints; service-related issues such as interruptions in monitoring tests, inadequate follow-up, and accessibility barriers; patient-related factors such as a false sense of recovery and reverting to previously quit habits; and provider-related issues such as lack of responsiveness and ineffective communication. Addressing these factors demands policy-level decisions and programmatic guidance at the national level based on best practices, as well as good programmatic implementation from actors through regional and health facility-level structures.